Stepwise multi-stage resection technique for surgical extraction of a partially erupted mandibular third molar with inferior alveolar nerve entrapment: a case report - Alsaegh, Mohammed A.; Fayyad, Elyazia; Jalal, Farah; Mulhem, Hana; Qasho, Manar; Mohannad, Nour; Moughrabel, Wissam (Frontiers in Oral Health, 2024)
The removal of lower third molars is one of the most common surgical procedures in routine dental practice. However, perforation of the mandibular third molars by the inferior alveolar nerve (IAN) is a rare occurrence. These cases are considered to carry a heightened risk of IAN injury due to the nerve being entrapped within the tooth. This case report details the experience of a 43-year-old female who visited the clinic for surgical removal of her lower third molar. She reported a six-month history of pain in area of tooth number 38, along with persistent hypersensitivity radiating through the lower lip and chin on the left side of her face, accompanied by abnormal sensations and numbness occurring alongside the pain. The case includes entrapment of IAN within the root of the partially erupted tooth, causing neurosensory disturbances. The associated lower third molar was extracted using a stepwise multi-stage resection technique in order to preserve the entrapped nerve. The patient's pain improved after surgery. This report contributes to current clinical knowledge and practices for extracting teeth with IAN entrapment. It addresses a gap in the limited and outdated literature on such cases.